How do you express yourself? - Ismawi, Hidayatul Radziah; Mohd Shehzad Lin, Farah Adrieanna Lin; Abdul Aziz, Farah; Mohd Nasir, Nur Nadhirah; Mohamad Nawi, Nurul Ain Nabilah; Abd Razak, Safwan Rukhaini (Malaysian Integrated Medical Professionals Association (MIMPA), 2022)
The IIUM SEMINAR SERIES are e-books based on Phase 1 Kulliyyah of Medicine, IIUM, MBBS student seminar presentations. As part of the curriculum, all students are required to present one seminar. Topics covered are varied and not necessarily related to medicine. This e-book is based on the topic of self-expression touching on the definition, importance and various forms of self- expression. It will also cover tips to enhance self-expression and some Islamic input on the topic.